Maternal Mid-Upper Arm Circumference and the Risk of Low Birth Weight Among Pregnant Women in Tana Toraja, Indonesia - Valensya Jeslin Tang Tiku; Meilani Kumala (Community Medicine and Education Journal, 2026)
Low birth weight (LBW) remains a persistent public health problem in low- and middle-income countries and a major determinant of neonatal morbidity and mortality, yet community-level evidence linking maternal nutritional status to LBW in rural eastern Indonesia is limited. This study analysed the association between maternal nutritional status, assessed by mid-upper arm circumference (MUAC), and the incidence of LBW at the Makale Community Health Center (Puskesmas), Tana Toraja Regency, Indonesia. An observational analytic cross-sectional design was applied to the antenatal and delivery records of 192 mothers who gave birth to singletons between January and December 2025, selected by purposive sampling. Chronic energy deficiency (CED) was defined as MUAC <23.5 cm and LBW as birth weight <2500 g. Data were analysed using the chi-square test, Fisher exact test, prevalence ratios (PR), and multivariable logistic regression with adjustment for maternal age and parity. The overall LBW prevalence was 13.02% (95% CI 8.98-18.52). LBW occurred in 57.14% (95% CI 42.21-70.88) of mothers with CED versus 0.67% (95% CI 0.12-3.68) of well-nourished mothers (PR 85.71, 95% CI 11.94-615.21; chi-square=92.41; Fisher p<0.001; Cramer V=0.694). After adjustment, low MUAC remained the dominant independent predictor of LBW (adjusted OR 205.71, 95% CI 25.22-1677.98; p<0.001; Nagelkerke R-squared=0.673), with an estimated population attributable risk of 94.9%. Strengthening maternal nutrition surveillance and targeted antenatal interventions at the primary-care level could substantially reduce LBW, supporting Sustainable Development Goals 2 and 3.